Comparison of Surgical Treatment of Postoperative Abdominal Wall Hernias with and without Fixation of a Synthetic Mesh: Literature Review - Varanauskas, Gintaras; Brimas, Gintautas (Lietuvos chirurgija, 2020)
Objective. Review articles with postoperative abdominal wall repair without mesh suturing (sutureless hernioplasty). Methods. A systematic search of the literature published from 01/01/2004 to 31/12/2018 was performed using Medline, PubMed and the Cochrane Library databases. The search was performed using the keywords: postoperative hernia, incisional hernia, mesh hernioplasty, sutureless repair, sutureless hernioplasty, sutureless herniotomy. Results. For the present analysis 5 publications were identified. The quality of each study was assessed. The information about operative methods, main results, conclusions and recommendations was collected. Conclusions. According to the results and conclusions of reviewed articles, it can be stated that postoperative abdominal wall hernia repair without mesh suturing is a safe and can improve postoperative results, but there is insufficient evidence to determine if it is associated with better outcomes than hernioplasty with mesh fixation. Further clinical studies are needed to clarify whether this method is clinically important.